Recurrent Bilateral Anterior Uveitis with Kikuchi–Fujimoto Disease. (2nd November 2017) - Gómez-Mariscal, Marta; Oleñik, Andrea; Arriba-Palomero, Pablo; García-Cosio, Mónica; Muñoz-Negrete, Francisco J.
ABSTRACT: Purpose : To report an uncommon case of Kikuchi–Fujimoto disease-associated-uveitis. Methods : A 31-year-old Caucasian woman with cervical lymphadenitis and Kikuchi–Fujimoto disease recently confirmed by biopsy, complained about unilateral blurry vision. Differential diagnoses, including non-Hodgkin lymphoma, tuberculosis, sarcoidosis, Behçet disease, rheumatoid arthritis, and juvenile idiopathic arthritis was performed. We undertook a review of other similar cases found in the literature. Results : Acute anterior unilateral uveitis was diagnosed, suffering from two recurrences of bilateral anterior uveitis. Conclusions : Additional reported cases are required to better understand the Kikuchi–Fujimoto disease and the pathogenesis and features of its ocular involvement.